Early and effective treatment of KCNQ2 encephalopathy. (16th April 2015) - Pisano, Tiziana; Numis, Adam L.; Heavin, Sinéad B.; Weckhuysen, Sarah; Angriman, Marco; Suls, Arvid; Podesta, Barbara; Thibert, Ronald L.; Shapiro, Kevin A.; Guerrini, Renzo; Scheffer, Ingrid E.; Marini, Carla; et al.
Summary Objectives To describe the antiepileptic drug (AED) treatment of patients with early infantile epileptic encephalopathy due to KCNQ2 mutations during the neonatal phase and the first year of life. Methods We identified 15 patients and reviewed the electroclinical, neuroimaging, and AED treatment data. Results Seizure onset was between 1 and 4 days of age with daily tonic asymmetric, focal and clonic seizures in nine patients and status epilepticus in the remaining six. Electroencephalography (EEG) showed multifocal epileptiform abnormalities in nine patients and a burst‐suppression pattern in six. All patients were trialed with adequate daily doses of several AEDs before they reached seizure freedom. Six patients (40%) achieved seizure control within 2 weeks of carbamazepine (CBZ) administration and five (33%) were seizure‐free with phenytoin (PHT). The last four patients (27%) were successfully treated with topiramate (TPM) (two patients), levetiracetam (LEV) (one), and a combination of LEV with TPM (one). Most patients reached seizure freedom within the first year of life and remained seizure‐free thereafter. Twelve patients had moderate‐to‐severe developmental delay at follow‐up. However, the two patients whose seizures ceased within a few days of onset showed only mild cognitive impairment. Significance Our findings suggest that drugs acting on sodium channels including CBZ and PHT should be considered as first‐line treatment in patients with KCNQ2 encephalopathy. Voltage‐gated sodium and potassium channels co‐localize at the neuronal membrane. Therefore, the efficacy of drugs acting as sodium‐channel blockers could be linked to their modulating effect on both channels. The type of KCNQ2 mutation might influence AED response as well as developmental outcome. Early recognition of KCNQ2 encephalopathy followed by the most appropriate and effective treatment may be important for reducing the neurodevelopmental impairment associated with this disorder.